Assessment of Sub-Micron Particles by Exploiting Charge Differences with Dielectrophoresis - Romero-Creel, Maria F. (Micromachines (Basel), 2017)
The analysis, separation, and enrichment of submicron particles are critical steps in many applications, ranging from bio-sensing to disease diagnostics. Microfluidic electrokinetic techniques, such as dielectrophoresis (DEP) have proved to be excellent platforms for assessment of submicron particles. DEP is the motion of polarizable particles under the presence of a non-uniform electric field. In this work, the polarization and dielectrophoretic behavior of polystyrene particles with diameters ranging for 100 nm to 1 μm were studied employing microchannels for insulator based DEP (iDEP) and low frequency (<1000 Hz) AC and DC electric potentials. In particular, the effects of particle surface charge, in terms of magnitude and type of functionalization, were examined. It was found that the magnitude of particle surface charge has a significant impact on the polarization and dielectrophoretic response of the particles, allowing for successful particle assessment. Traditionally, charge differences are exploited employing electrophoretic techniques and particle separation is achieved by differential migration. The present study demonstrates that differences in the particle’s surface charge can also be exploited by means of iDEP; and that distinct types of nanoparticles can be identified by their polarization and dielectrophoretic behavior. These findings open the possibility for iDEP to be employed as a technique for the analysis of submicron biological particles, where subtle differences in surface charge could allow for rapid particle identification and separation.